1993
DOI: 10.1002/1097-0142(19930601)71:11<3565::aid-cncr2820711117>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

The influence of progesterone and androgens on the growth of endometrial carcinoma

Abstract: Background. The prognosis for endometrial cancer is correlated to the proliferative activity, expressed as the fraction of cells in the synthesis phase (S‐phase fraction [SPF]). Progesterone has an antiproliferative effect on the normal endometrium. Its effect in endometrial adenocarcinoma has not been investigated in such detail. Methods. The SPF in tumor tissue and serum levels of progesterone, androstenedione, and testosterone were measured in 78 postmenopausal women with the diagnosis of endometrial adenoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Endogenous testosterone levels have not been shown to be associated with the risk of endometrial carcinoma, when the data are appropriately adjusted for the independent effect of estrogen levels, which track with the androgen concentrations [40]. No increase in endometrial proliferation was found in women taking 1.25 mg of methyltestosterone daily along with esterified estrogens vs. women taking esterified estrogens alone [6].…”
Section: Endometriummentioning
confidence: 94%
See 1 more Smart Citation
“…Endogenous testosterone levels have not been shown to be associated with the risk of endometrial carcinoma, when the data are appropriately adjusted for the independent effect of estrogen levels, which track with the androgen concentrations [40]. No increase in endometrial proliferation was found in women taking 1.25 mg of methyltestosterone daily along with esterified estrogens vs. women taking esterified estrogens alone [6].…”
Section: Endometriummentioning
confidence: 94%
“…Although in vitro data indicate that androgens antagonize the effects of estrogens on endometrial cells, there is a concern that the high aromatization ability of the endometrium may convert exogenous testosterone to estrogen locally and adversely affect the uterus [39]. Endogenous testosterone levels have not been shown to be associated with the risk of endometrial carcinoma, when the data are appropriately adjusted for the independent effect of estrogen levels, which track with the androgen concentrations [40]. No increase in endometrial proliferation was found in women taking 1.25 mg of methyltestosterone daily along with esterified estrogens vs. women taking esterified estrogens alone [6].…”
Section: Endometriummentioning
confidence: 99%
“…Although androgens do not directly stimulate endometrial cells (103)(104)(105)(106)(107)(108)(109)(110), endometrial cancer cells exhibit aromatase activity (104,107,108). Thus, there is a concern that androgens may be converted into estrogens by endometrial cancer cells and thereby stimulate endometrial cancer cellular proliferation (109,110).…”
Section: Effects On the Endometriummentioning
confidence: 99%
“…Androgens do not seem to have a direct stimulatory effect on endometrial cell proliferation,9, 10, 11, 12 After menopause, however, when the ovarian production of estrogens ceases, an association between circulating androgen levels and risk of endometrial cancer is expected because of the aromatization of androgens into estrogens in peripheral (in particular adipose) tissues. In addition, the persistence of a strong positive association between serum androstenedione levels and endometrial cancer risk after adjustment for circulating estrone observed in a large case‐control study, led Potischman et al8 to hypothesize that abnormal endometrial cells could produce estrogens in situ from the plasma pool of androstenedione, and thus gain a growth advantage independent of circulating estrogens.…”
mentioning
confidence: 99%
“…Numerous retrospective case‐control studies have shown an increase in endometrial cancer risk with higher concentrations of endogenous estrogens, mostly with levels of estrone and total estradiol 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17. We reported previously the results of the first prospective study on endometrial cancer in postmenopausal women, a case‐control study nested within the New York University Women's Health Study (NYUWHS), and showed that elevated pre‐diagnostic circulating levels of estrone, total estradiol and free estradiol were related to an increased risk, whereas sex hormone binding globulin levels (SHBG) and SHBG‐bound estradiol were inversely related to risk 18…”
mentioning
confidence: 99%